Overview of Problem-based Learning: Definitions and Distinctions - Savery, John R. (Interdisciplinary Journal of Problem-based Learning, 2006)
Problem-based learning (PBL) is an instructional approach that has been used successfully for over 30 years and continues to gain acceptance in multiple disciplines. It is an instructional (and curricular) learner-centered approach that empowers learners to conduct research, integrate theory and practice, and apply knowledge and skills to develop a viable solution to a defined problem. This overview presents a brief history, followed by a discussion of the similarities and differences between PBL and other experiential approaches to teaching, and identifies some of the challenges that lie ahead for PBL.
Keywords: apprentissage par projet; résolution de problème; étude de cas